2017
DOI: 10.1038/s41531-017-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic proteins in CSF relate to Parkinson’s disease stage markers

Abstract: Recent findings of morphological and functional changes in Parkinson’s disease brains have shown altered synapse formation, but their role in cognitive decline is still an area under exploration. Here we measured the concentration of three key synaptic proteins, Rab3A, SNAP25 and neurogranin by enzyme-linked immunosorbent assay, in cerebrospinal fluid from a total of 139 participants (87 controls and 52 Parkinson’s disease patients out of which 30 were drug-naïve) and explored their associations with motor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 33 publications
7
48
0
1
Order By: Relevance
“…Furthermore, increased Ng has been linked to cognitive decline and conversion from MCI to AD . In this study focusing on parkinsonian disorders, confirming some studies but contradicting others, we find decreased levels of Ng in PD compared to controls. We also found decreased levels of Ng in MSA and PSP using both assays and in PDD using Ng‐EI.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, increased Ng has been linked to cognitive decline and conversion from MCI to AD . In this study focusing on parkinsonian disorders, confirming some studies but contradicting others, we find decreased levels of Ng in PD compared to controls. We also found decreased levels of Ng in MSA and PSP using both assays and in PDD using Ng‐EI.…”
Section: Discussionsupporting
confidence: 85%
“…Contradicting one study, but supporting another, we found no association between levels of Ng and motor dysfunction . Furthermore, supporting results from one study, we found no associations between Ng and cognitive impairment in parkinsonian disorders.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings suggest that cortical synaptic changes lead to cognitive decline in PD, consistent with imaging findings (see below), and preliminary work indicates that synaptic changes are also reflected in the cerebrospinal fluid (CSF). Neurogranin levels were found to be increased in the CSF in AD 33 , probably due to increased intracellular sequestration, and similar findings have been reported — and linked with cognitive decline — in PD 34 . Thus, CSF levels of synaptic proteins are potential biomarkers of future cognitive decline.…”
Section: Mechanismssupporting
confidence: 84%
“…A posztszinaptikus neurogranin fehérje vizsgálata a liquorban nem hozott meggyőző eredményt. Noha AD-ben és PD-ben is emelkedett szintet mértek az egészséges csoporthoz képest, a DLB-ben mért szint nem képes biztosan különbséget tenni sem a kontrollcsoporttól, sem az egyéb, demenciával járó betegségek-től [66]. A kiterjedt vizsgálatok ellenére eddig nem sikerült olyan liquor-biomarkert azonosítani, amelyik specifikus lenne DLB-re és biztonsággal el tudná azt kü-löníteni más neurodegeneratív kórképektől.…”
Section: Elektroencefalográfia (Eeg) éS Liquor-biomarkerekunclassified